A proclamation for a continental fast. In Congress, Saturday, March 16, 1776 : ... The Congress ... do earnestly recommend that Friday the seventeenth day of May next be observed by the said colonies as a day of humiliation, fasting, and prayer . ([publisher not identified], 1776)
March 16, 1776 Proclamation by Congress setting a day of prayer and fasting in the colonies on May 17th to have God's blessings and against the British invasion.